Percepción de los turistas y la técnica tradicional ikat en el cantón Gualaceo de la Provincia de Azuay - Ronquillo Ortiz, Julissa Andrea (2019)
The tangible and intangible cultural heritage is a set of assets that are called ancestral heritage and can be historical as natural, the objective of this investigation is to promote the use of the IKAT traditional technique as an intangible heritage of the Bullcay and Bullzhún communities to make known the cultural richness inherited from its ancestors. The ancestral knowledge is cultural manifestations that are based primarily on the knowledge and practice of customs, traditions, rituals, historical facts, myths and legends, elements that are considered as the most important part of a people and its inhabitants for being a fundamental piece of their cultural identity. Through the material and intangible heritage, communities can develop cultural tourism also known as historical tourism for its great importance in the life of the human being, this typology of tourism will allow increasing economic income to the communities that carry out, contributing to improving the quality of life of its inhabitants. Through the ancestral knowledge and their permanent dissemination will be achieved to maintain, preserving and preserving these manifestations to be transmitted to future generations, and whether the spokespersons of these events that give a true cultural value to the Gualacense people